Analisis Pengaruh Penyajian Laporan Keuangan, Aksesibilitas Laporan Keuangan, dan Sistem Pengendalian Internal terhadap Akuntabilitas dalam Pengelolaan Keuangan Desa (Studi pada Pemerintah Desa di Kecamatan Mranggen) - Khoirina, Ana; Widaryanti, Widaryanti (STIE PENA, 2023)
Accountability in managing village finances is very important. This requires the ‎village government to manage village finances professionally, effectively and efficiently, and ‎accountably. The purpose of this study was to determine the readiness of the village ‎government in realizing accountability for village financial management, so research was ‎conducted on the effect of presenting financial reports, accessibility of financial reports, and ‎internal control systems on village financial management accountability.‎ The subject of this research is the village government in Mranggen District. The sampling ‎technique in this research is saturated sampling technique (census). The data collection ‎instrument in this study was a questionnaire or questionnaire. The research data used ‎primary data, directly through questionnaires and analyzed using SPSS version 26. Data ‎were analyzed to test the hypothesis using multiple regression analysis approach.‎ The results of this study indicate that the presentation of financial reports influences the ‎accountability of village financial management. The accessibility of financial reports has no ‎effect on the accountability of village financial management. The internal control system ‎influences the accountability of village financial management.‎ Keywords:‎ Presentation of Financial Statements, Accessibility of Financial Statements, ‎Internal Control System, Village Financial Management Accountability